Assessing the Impact of Land Cover on Groundwater Quality in a Smart City Using GIS and Machine Learning Algorithms - Anjum, Rukhsar; Ali, Sk Ajim; Siddiqui, Mansoor Alam (Water, air, and soil pollution, 2023)
The present study aimed to assess the impacts of land cover on groundwater quality by integrating physico-chemical data and satellite imageries. Initially, fourteen groundwater parameters of both pre-monsoon and post-monsoon were collected from nineteen sampled stations and water quality index (WQI) was calculated. Consequently, Google earth, Landsat-8, and Sentinel-2A imageries were considered for land cover mapping including the concentration of settlement and urban built-up, greenery coverage, and micro-level land use. Two machine learning models such as artificial neural network (ANN) and random forest (RF) were used for pixel-based classification and establish spatial relation between water quality and land cover. This study trained and tested the models for the whole study area as well as 500m buffers from each sampled station. The result of model’s validation including mean absolute error (MAE), root mean squared error (RMSE), Kappa statistic (K), overall accuracy of model (OAC), and receiver operating characteristic (ROC), indicated that random forest classifier has better performance than the artificial neural network. The results show that the testing dataset of pre-monsoon season has higher accuracy with MAE 0.343, RMSE 0.397, K value 0.55, and ROC value 0.838 to envisage the impact of land cover on groundwater quality in comparison to post-monsoon season. The results also reveal that the classification accuracy is greater within 500m buffer areas in comparison to the whole study area with a close to 0 values of MAE and RMSE, and absolutely 1 value of K and ROC. Based on the above findings, the present study suggested considering a large scale for determining the controlling factors of groundwater degradation.